PENGEMBANGAN LKPD BERBASIS LINGKUNGAN UNTUK MENINGKATKAN PENGETAHUAN SIKLUS AIR DAN DAMPAKNYA MELALUI PEMBELAJARAN IPA PADA SISWA KELAS V - Laila Sofiatun Janna; Endang Widi Winarni; Irwan Koto (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to determine the feasibility of the material, language, design, student responses, and the effectiveness of products developed from environment-based worksheets to increase knowledge of the water cycle and its impacts for fifth graders of elementary school. This research is an ADDIE Research and Development (R&D) model. To measure the effectiveness of knowledge of the water cycle and its impact, tests were carried out twice, namely before and after learning took place in the control and experimental classes. The results of material validation, language, design and students' responses to environment-based worksheets are very appropriate and well used in learning so that students are happy and interested in learning science on the water cycle material and its impacts. The results of the effectiveness of the effectiveness of LKPD on knowledge of the water cycle and its impact on students. Judging from the results of the significance that is 0.008 is smaller than α = 0.05. Based on the gain score test from the use of LKPD, the results of the gain score were moderate, namely the control class was 47% and the experimental class was 59%. Thus, knowledge of the water cycle and its impacts using an environmentally based LKPD is declared effective.